Tuberculosis among children, adolescents and young adults in the Philippines: a surveillance report - Snow, Kathryn; Yadav, Rajendra; Denholm, Justin; Sawyer, Susan; Graham, Stephen (Western Pacific Surveillance and Response, 2018)
The Philippines, a country with a young population, is currently experiencing an intense and persistent tuberculosis epidemic. We analysed patient-based national surveillance data to investigate the epidemiology of reported tuberculosis among children (aged 0–9 years), adolescents (aged 10–19 years) and young adults (aged 20–24 years) to better understand the burden of disease and treatment outcomes in these age groups.Descriptive analyses were performed to assess age-related patterns in notifications and treatment outcomes. Data quality was assessed against international benchmarks at the national and regional levels.Overall, 27.3% of tuberculosis notifications for the Philippines in 2015 pertained to children, adolescents and young adults aged 0–24 years. Treatment outcomes were generally favourable, with 81% of patients being cured or completing treatment. The data quality assessment revealed substantial regional variation in some indicators and suggested potential underdetection of tuberculosis in children aged 0–4 years.Children, adolescents and young adults in the Philippines constitute a substantial proportion of patients in the national tuberculosis surveillance data set. Long-term progress against tuberculosis in the Philippines relies on improving the control of tuberculosis in these key age groups.